WANDERING ABOUT MINERALOGY AND PETROLOGY - Katagas, Ch. (Bulletin of the Geological Society of Greece, 2010)
Over the past few years an intense amount of research on various themes stimulated the development of Mineralogy and all its diversity, and many exciting discoveries have been made. New or technologically developed analytical and experimental methods such as ion microprobe, powerful MAS NMR, LA-ICP-MS, IR, Raman, XAS spectroscopies, beams of high intensity, Synchrotron radiation that enhanced the sensitivity of conventional spectroscopic and XRD techniques, beams of neutrons, widely available information and tremendous computing and modelling facilities have turned out to be excellent tools, promoting the ability of mineralogy in solving global and societal challenges. Mineralogy today offers insights into important scientific issues, including sustainable development, evolution of the Earth and origins of life, deep Earth processes, physics and chemistry of Earth materials, fluids, magmas, igneous rocks and time scales, archaeomineralogy, nano-, geo-, and bio- environmental sciences. The mineralogical sciences today are going through a period of rapid expansion and diversification and this trend is going to continue in future. There is now great potential for much interesting work in the latter areas but also the need to somehow protect the coherence of our discipline.